35th Annual David W Smith Workshop on Malformations and Morphogenesis: Abstracts of the 2014 Annual Meeting. (22nd May 2015) - Braddock, Stephen R.; Lipinski, Robert J.; Williams, Marc S.; Carey, John C.
Abstract The 35th Annual David W Smith Workshop on Malformations and Morphogenesis was held on July 25–30, 2014 at the University of Wisconsin, Madison, Wisconsin. The conference, which honors the legacy of David Smith, brought together over 130 clinicians and researchers interested in congenital malformations and their underlying mechanisms of morphogenesis. As is the tradition of the meeting, the Workshop highlighted five themes besides mechanisms of morphogenesis: Evolution and Development, Minor Malformations, CHARGE syndrome, Craniofacial Development/ Malformations, and Disorders of Chromatin Remodeling. This Conference Report includes the abstracts presented at the Workshop. © 2015 Wiley Periodicals, Inc.